DAMPAK KEBIJAKAN ANTI-RESETTLEMENT AUSTRALIA TERHADAP PENGUNGSI ASING ASAL AFGHANISTAN DI PEKANBARU - Marpaung, A. Rivalno Marpaung; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research is to determine the condition of foreign refugees from Afghanistan in Indonesia as well as the history of the early background of refugees coming to Indonesia. Also to find out the cause of Australia cutting off the resesttelement of refugees in Indonesia. How the impact of the anti-resettlement policy on foreign refugees from Afghanistan in Pekanbaru and the attitude of refugees after the Anti-Resettlement policy in Pekanbaru. This study was analyzed using qualitative methods with interview techniques of foreign refugees from Afghanistan, observation and literature. Using migration theory according to Khalid Koser in 2003 stated in his book entitled "New African Diasporas" related to migration security which is divided into 3 main dimensions of migration security, namely human, state, and global security. Explain about input, which is how a regulation or law is made and then produces output, namely the impact of the results of the law. In theory, this relates to Australia issuing an anti-resettlement policy against foreign refugees from Afghanistan registered with UNHCR Indonesia. The results of this study can be concluded that anti-resettlement policies are issued by Australia on economic and Islamophobic grounds or related to national security. This has a major impact on foreign refugees from Afghanistan in Indonesia regarding their life security, their children's education, their jobs, marriages, and their mental or mental health in the future. Keyword: Refugees, Anti-Resettlement, Afghanistan, Australia, UNHCR, Pekanbaru.